Introducing positive media psychology to the field of children, adolescents, and media. Issue 1 (2nd January 2016) - de Leeuw, Rebecca N. H.; Buijzen, Moniek
Abstract: The field of children, adolescents, and media has predominantly focused on harmful media effects, for instance, concerning the potential harm of media violence. Although we recognize the relevance of that research, we propose that the balance in the field should be restored with research that also considers the beneficial effects of media exposure. In this essay we introduce positive media psychology to the arena of children, adolescents, and media. By incorporating insights from the field of positive psychology and pioneering work on meaningful media entertainment among adults, we provide a theoretical backdrop for future research to examine how media can help children and adolescents to thrive and flourish.